2020
DOI: 10.1111/cns.13526
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and pathophysiology of idiopathic normal pressure hydrocephalus

Abstract: First defined in 1965, idiopathic normal pressure hydrocephalus (iNPH)is a surgically reversible neurological disorder in adults. It is characterized by dementia, gait disturbance, and urinary incontinence (known as Hakim's triad). 1,2 INPH is not a rare clinical entity. The prevalence of iNPH has been estimated to be 10 per 100 000 to 22 per 100 000 overall, with 1.30% in those aged ≥65 years and 5.9% in those aged ≥80 years. 3,4 One of the core features of iNPH is that the cerebrospinal fluid (CSF) pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
86
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 119 publications
1
86
0
4
Order By: Relevance
“…The ventricles of these rats remained enlarged, even after the blood pressure was lowered by captopril 89 . Current studies have found that choroid plexus cell death, ependymal injury, impaired glymphatic transport, hemorrhage, and other factors may be involved in the development of hydrocephalus in spontaneously hypertensive rats 17,87,90,91 . Therefore, minocycline is a promising drug for the treatment of hydrocephalus and related tissue damage.…”
Section: Anti‐iron Overload Treatment For Hydrocephalusmentioning
confidence: 99%
See 3 more Smart Citations
“…The ventricles of these rats remained enlarged, even after the blood pressure was lowered by captopril 89 . Current studies have found that choroid plexus cell death, ependymal injury, impaired glymphatic transport, hemorrhage, and other factors may be involved in the development of hydrocephalus in spontaneously hypertensive rats 17,87,90,91 . Therefore, minocycline is a promising drug for the treatment of hydrocephalus and related tissue damage.…”
Section: Anti‐iron Overload Treatment For Hydrocephalusmentioning
confidence: 99%
“…These substances into the brain parenchyma are collected in the perivenous spaces surrounding the large deep veins and flow into the neck lymphatic system 109 . Some evidence suggests that there may be impaired glymphatic transport in patients with idiopathic normal pressure hydrocephalus (iNPH) and that the abnormal expression of AQP4 may be involved in this damage 91,113–115 . By using magnetic resonance imaging contrast agent as CSF tracer, it was found that there is a significant delay in the tracer clearance stage of iNPH patients 115,116 .…”
Section: Aquaporin Regulation Treatment For Hydrocephalusmentioning
confidence: 99%
See 2 more Smart Citations
“…In NPH, glymphatic dysfunction could play a role in worsening the hydrocephalus and symptoms. The low compliance of the brain and high glymphatic resistance leads to more CSF accumulation in the peri-arterial space and subsequently decreased arterial pulsatility [5]. Similar to Alzheimer's disease, this leads to the accumulation of toxic metabolites and worsened cognition [3].…”
mentioning
confidence: 99%